(untitled) - Ivor Chucas (Rome, 1997)
Fish are discarded for various reasons at sea, representing a waste of fishery resources and potential food. Although the exact quantities wasted might be disputed, the amount of fish wasted through discarding is large. One of the options that is apparent for overcoming the problems of discards ib fisheries is that more of the fish should be used for human consumption, assuming that it is consistent with responsible fisheries management practices. This would not only overcome the apparent waste of resources but would also add more valuable fish protein to the food balance of many people. This paper brings together information, on the spices and where possible the quantities of fish that are presently discarded. Information on attempts and trends that have been and are being made to make use of these potential discards are used to illustrate the successes and failures which migh help to guide further efforts in fuller utilisation of the fish resources. It is apparent that more systematic information is required regarding the quatity and composition of discards in many fisheries. It also seems from past experience that successful use of bycatch is usally market lead and that efforts should continue to assist in identifying suitable marketing and product development opportunities where appropriate.
Keywords: fisheries,ichthyology